PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3), DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN PT UT QUALITY INDONESIA DI BATAM - Icha Vanida Putri (2022)
PT UT Quality Indonesia is a company engaged in the oil & gas industry. This study aims to determine the effect of occupational safety and health (K3), work discipline on work productivity of PT UT Quality Indonesia employees in Batam. The data collection technique used stratified random sampling to obtain a research sample of 60 respondents. Data collection is done by distributing questionnaires through Google Forms. The data analysis technique used Partial Least Square (PLS). The results of this study indicate that occupational safety and health (K3) has a positive and significant effect on work productivity for PT UT Quality Indonesia employees. Work discipline has a positive and significant effect on work productivity of PT UT Quality Indonesia employees. Occupational safety and health (K3), work discipline simultaneously affect the work productivity of PT UT Quality Indonesia employees.